2022
DOI: 10.1111/asj.13720
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones and their metabolites influence the milk production ability of bovine mammary epithelial cells in a type‐specific manner

Abstract: Dairy cows feed on isoflavones as physiologically active substances present in legumes. However, the influences of isoflavones (biochanin A, genistein, formononetin, and daidzein) and their metabolites (p-ethylphenol and equol) on milk components production, tight junctions (TJs), and their regulatory pathways are unclear in bovine mammary epithelial cells (BMECs). In this study, we investigated the influences of isoflavones and their metabolites in BMECs using an in vitro culture model. The influences of isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Tsugami et al. [ [110] , [111] , [112] , [113] ] and Kumai et al. [ 114 ] have demonstrated using mouse and cow models that isoflavones have different effects on mammary gland development, TJ formation, and expression of milk components, thereby affecting milk production ( Table 2 ).…”
Section: External Factors Affecting Milk Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsugami et al. [ [110] , [111] , [112] , [113] ] and Kumai et al. [ 114 ] have demonstrated using mouse and cow models that isoflavones have different effects on mammary gland development, TJ formation, and expression of milk components, thereby affecting milk production ( Table 2 ).…”
Section: External Factors Affecting Milk Productionmentioning
confidence: 99%
“…[ 114 ] have demonstrated using mouse and cow models that isoflavones have different effects on mammary gland development, TJ formation, and expression of milk components, thereby affecting milk production ( Table 2 ). Specifically, biochanin A and its metabolite genistein have been shown to inhibit mRNA expression and secretion of both β-casein and lactoferrin [ 110 , 112 ]. Biochanin A also reduced activated STAT5 and increased activated STAT3, which are the negative indicators for milk component production and TJ barriers [ 110 ].…”
Section: External Factors Affecting Milk Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to daidzein, equol may promote milk production as it activates Stat5 and increases Csn1-3 expression while inactivating Stat3 and decreasing tight junction permeability through claudin-3. [27,122],] Studies of mouse MECs cultured in Matrigel showed that similar to genistein, coumestrol inhibits ductal branching and alveolar formation by inducing apoptosis and reducing the proliferation and migration of MECs. Further studies are required to fully understand the consequences of soy products and isoflavones on milk production and composition.…”
Section: Effects Of Isolated Polyphenols On Lactationmentioning
confidence: 99%
“…Moreover, some polyphenols, such as those found in soy, have estrogenic activity and may positively or negatively affect hormone signaling in the mammary gland, influencing expression, and milk production. [26][27][28] Thus, understanding the molecular mechanisms through which polyphenols affect mammary gland biology will provide a valuable perspective for developing interventions to improve lactation outcomes.…”
Section: Introduction 1breastfeeding and The Use Of Galactagoguesmentioning
confidence: 99%